Use of flow-cytometry to distinguish between haploid and diploid strains of Aspergillus fumigatus - J R de Lucas; A I Domínguez; A MENDOZA; F LABORDA (Fungal Genetics Reports, 1998)
Many filamentous fungi with general interest such as plant/human pathogens and enzyme/antibiotic producers lack a sexual cycle. Since sexual crosses are unavailable in these species, the parasexual analysis, apart from physical mapping, is the only way of mapping the chromosomes. The use of the parasexual cycle requires a method to distinguish between haploids and diploids. Here, we report the use of flow-cytometry to distinguish clearly between haploid and diploid strains of Aspergillus fumigatus, a very rapid, simple and accurate technique that can be applied to parasexual analysis in other filamentous fungi.